The effect of lipopolysaccharide on liver homeostasis and diseases based on the mutual interaction of macrophages, autophagy, and damage-associated molecular patterns in male F344/DuCrlCrlj rats. Issue 4 (July 2023) - Takami, Yuki; Tanaka, Miyuu; Izawa, Takeshi; Kuwamura, Mitsuru; Yamate, Jyoji
Lipopolysaccharide (LPS) has dose-dependent biphasic functions (cell protective versus cell toxic). To clarify the different effects of LPS on liver homeostasis or liver diseases, comparisons were made between low and high doses of LPS, in terms of the mutual relation of hepatic macrophages, autophagy, and damage-associated molecular patterns (DAMPs) in male F344/DuCrlCrlj rats. Rats injected with low dose (0.1 mg/kg) or high dose (2.0 mg/kg) of LPS were examined at 6, 10, and 24 hours following single injections. Histologically, focal hepatocellular necrosis was occasionally present in high-dose animals, whereas there were no significant changes in low-dose animals. In low-dose animals, Kupffer cells reacting to CD163 and CD204 were hypertrophic and regarded as M2 macrophages, which promote resolution of inflammation and tissue repair, whereas in high-dose animals, infiltration of M1 macrophages expressing CD68 and major histocompatibility complex class II, which enhance cell injury, was seen. Hepatocytes with high-mobility-group box-1 (HMGB1) (one of DAMPs)-positive cytoplasmic granules appeared more frequently in high-dose animals than in low-dose animals, indicating the translocation of nuclear HMGB1 into the cytoplasm. However, although light-chain 3 beta–positive autophagosomes in hepatocytes increased in both doses, abnormally vacuolated autophagosomes were only seen in injured hepatocytes in the high-dose group, indicating possible extracellular release of HMGB1, which might result in cell injury and inflammation. These findings suggested that low-dose LPS induced a favorable mutual relationship among hepatic macrophages, autophagy, and DAMPs leading to cytoprotection of hepatocytes, whereas failures of the relationship in high-dose LPS caused hepatocyte injury.